Legal institutions, innovation and growth - Luca Anderlini; Leonardo Felli; Giovanni Immordino; Alessandro Riboni (Center for Economic Studies and ifo Institute (CESifo), 2011)
We analyze the relationship between legal institutions, innovation and growth. We compare a rigid (law set ex-ante) legal system and a flexible one (law set after observing current technology). The flexible system dominates in terms of welfare, amount of innovation and output growth at intermediate stages of technological development - periods when legal change is needed. The rigid system is preferable at early stages of technological development, when (lack of) commitment problems are severe. For mature technologies the two legal systems are equivalent. We find that rigid legal systems may induce excessive (greater than first-best) R&D investment and output growth.
Keywords: O30; O43; L51; E61; 330; legal system; commitment; flexibility; innovation; growth